Effectiveness of flipchart and leaflet-based nutrition education on knowledge, attitudes, and practices of Posyandu cadres in Central Papua - Naning Isroul Fauziah; Sufiati Bintanah; Ary Istiany; Kartika Nugraheni; Rahayu Astuti (AcTion: Aceh Nutrition Journal, 2026)
Posyandu cadres play a crucial role in promoting balanced nutrition education within communities, particularly in areas with limited access to health services, such as Central Papua. Appropriate educational media are needed to enhance knowledge, attitudes, and practices. This study compared the effectiveness of flipchart- and leaflet-based nutrition education in improving balanced nutrition knowledge, attitudes, and practices among the cadres. A quantitative quasi-experimental study was conducted in the Timika Community Health Center service area in August 2025. Sixty cadres were selected through simple random sampling and assigned to either the flipchart (n=30) or leaflet (n = 30) group. Educational interventions were delivered using flip charts and leaflets. Data were analyzed using Wilcoxon and Mann–Whitney tests. Results: Both media significantly improved the cadres’ knowledge and practices (p<0.001). Knowledge improvement was greater in the flipchart group (mean difference: 3.37±0.32) than in the leaflet group (2.10±1.03; p<0.001). Attitude scores increased significantly in the flipchart group (1.13±2.24; p=0.013), whereas the increase in the leaflet group was not statistically significant (0.53±2.10; p=0.139). Practice improvement was higher in the flipchart group (7.33±1.83) than in the leaflet group (1.20±1.03; p<0.001). In conclusion, flipchart-based education was more effective than leaflets in improving Posyandu cadres’ knowledge and practices regarding balanced nutrition, supporting stronger community-based nutrition promotion in remote areas of Indonesia.